Transação tributária no Direito brasileiro - Câmara, Lauro Tércio Bezerra (2020)
This document aims to study the admissibility, the legal nature, the assumptions and the effects of the transaction involving taxes in national law, in view of the doctrinal resistance and the timid use of the institute by the State. It analyzes the phenomenon based on legal dogmatics, conceiving it as a fact with the purpose of resolving the dispute and inserting a rule in the legal system, which alters the regime for complying with the tax obligation. It describes the transaction within the scope of civil, administrative and procedural dogmatics, delimiting the basic discipline on which the legal commands of a tax nature stand. It recognizes the constitutionality of the tax transaction in Brazilian law, which concretizes the principles of the democracy, the public purpose, the reasonable length of proceedings, the capacity of contribution and the efficiency. It identifies the constitutional limits for authorization of the transaction, prescribed especially by the principles of legality, reasonableness, equality, morality, publicity and access to Justice. It situates the transaction in the context of the tax legal relationship, understanding by its application only to the main tax obligation - including fines and taxes -, which has changed its way of extinguishing under the pact. The legal nature of the transaction is considered to be contractual, considering that the manifestation of will does not appear as a mere presumption of validity or effectiveness of the act. It lists the assumptions for the conclusion of the convention, including the subjects, who must be legitimate and able to compromise; the reason, based on a dispute, characterized by default or objective doubt about the exaction; the purpose, consistent in resolving the conflict, in order to serve the collective interest; the objects, the pact falling on the main tax obligation and the litigation; and the content, which includes clauses for extinguishing the dispute and changing the way of complying with the obligation, in addition to the possibility of fixing accessory and accidental elements. It clarifies the effects of this convention, alluding to those of a procedural nature, including the settlement of the dispute and the formation of a judicial note, and of a substantial nature, establishing a new program to comply with the tax obligation, with the relevant effects according to the clauses adjusted. It distinguishes the transaction from the novation, considering the absence of the animus novandi in that one. It addresses state laws that convey norms that authorize tax transactions, discussing their compliance or not with respect to the topics covered during the study. It details the prescriptions of Federal Law No. 13,988/2020, highlighting the advances in the legislative treatment of the matter and making criticisms. At the end, it lists the results achieved throughout the study, concluding by the reduced exploitation of this efficient means of conflict resolution by the national legal system